Mechanical properties of PP/RPET blends and PP-g-MAH as compatibilizer / Aina Aref ... [et al.] - Aref, Aina; Said, Salihin; Zainy, Fadhilah; Mustafa, Haikal; Tan, Suhee; Wahit, Mat Uzir (2018)
There are many problems regarding recycling of plastic materials products such as recycle polyethylene terephthalate (RPET) which has been a major problems of regarding recycle method. This study was carried out to observe on the ratio that give high strength of polypropylene (PP) reinforced with recycle polyethylene terephthalate (RPET) blend with maleic anhydride grafted propylene (PP-g-MAH). The addition of PP-g-MAH intended to improve the compatibility between PP and RPET. These composites were mix and compounded using a single screw extruder before been injected using injection molding machine. The product of the molded compound was cut according to the ASTM D618 standard and has been tested on tensile and flexural test using tensile strength machine. The formulation of PP and 10%RPET shown to improve the flexural and tensile properties.